A study on good governance in controlling corruption in education sector in India. (9th August 2019) - Tyagi, Lokinder Kumar
Corruption and poor governance practices go hand in hand. The more the loop holes present in government policies, the more flexible and adaptable it becomes for the people to exercise their capacity of power and money in an unauthorised and illegal way leading to the destruction of the main ethics of education by exploiting the general public through encouragement of various malpractices like bribery, nepotism, fraud, and favouritism. Ultimately, this situation violates the rights of the deserving people as well as affects the society and economy of the country. Therefore, there is an urgent call for enforcement of good governance practices which can curb the corrupt activities in education sector. This study has been conducted with the objective to understand the concepts of 'governance' and 'corruption' and also to study the role of good governance practices in controlling corruption in Indian Education System by proposing a tentative model between the two.